Studies on the press in Sri Lanka and South Asia - Peiris, G. H.; International Centre for Ethnic Studies (Kandy : International Centre for Ethnic Studies, 1997)
Contributed articles.
Keywords: Press -- Sri Lanka -- History; Mass media -- Political aspects -- Sri Lanka; Journalism -- Political aspects -- South Asia